Measurement of the forward-backward asymmetry in low-mass bottom-quark pairs produced in proton-antiproton collisions - Aaltonen, T.; Amerio, S.; Amidei, D.; Anastassov, A.; Annovi, A.; Antos, J.; Apollinari, G.; Appel, J. A.; Arisawa, T.; Artikov, A.; Asaadi, J.; Ashmanskas, W.; et al. (My University, 2016)
We report a measurement of the forward-backward asymmetry, AFB, in bb pairs produced in proton-antiproton collisions and identified by muons from semileptonic b-hadron decays. The event sample is collected at a center-of-mass energy of s=1.96 TeV with the CDF II detector and corresponds to 6.9 fb-1 of integrated luminosity. We obtain an integrated asymmetry of AFB(bb)=(1.2±0.7)% at the particle level for b-quark pairs with invariant mass, mbb, down to 40 GeV/c2 and measure the dependence of AFB(bb) on mbb. The results are compatible with expectations from the standard model. © 2016 American Physical Society.
Citation: Aaltonen, T., Amerio, S., Amidei, D., Anastassov, A., Annovi, A., Antos, J., . . . Zucchelli, S. (2016). Measurement of the forward-backward asymmetry in low-mass bottom-quark pairs produced in proton-antiproton collisions. Physical Review D - Particles, Fields, Gravitation and Cosmology, 93(11). doi:10.1103/PhysRevD.93.112003